Pathogenesis of Feline Panleukopenia Virus in Susceptible Newborn Kittens II. Pathology and Immunofluorescence - Csiza, C. K. (1971)
Twenty-three susceptible newborn kittens were inoculated with feline panleukopenia virus on the day of birth and were sacrificed from 18 hr to 43 days postinoculation (DPI). Macroscopic lesions included thymic atrophy in animals examined at 4 to 14 DPI and cerebellar hypoplasia and degeneration in animals examined at 22 to 43 DPI. Clinical signs of ataxia were not observed in the four kittens with cerebellar lesions sacrificed at 22 to 43 days of age. Intranuclear inclusions were present in a variety of cell types in the organs examined from kittens that died or were sacrificed at 4 to 14 DPI. The most severely infected and depleted tissues were the thymus, spleen, mesenteric lymph nodes, and the cerebellum, whereas the bladder, testes, ovaries, and uterus were the least susceptible to panleukopenia virus infection. Specific fluorescence was demonstrated with panleukopenia antiglobulin conjugate in various cell types in tissues from 2 to 22 DPI and only in cerebellar Purkinje cells of kittens sacrificed at 29, 36, and 43 DPI. The virus replicated in the cells of all layers of blood vessels (endothelial, muscular, and connective tissue cells), suggesting that this is the route of dissemination of the agent throughout the body.